Perhitungan Beban Pencemaran Air Kali Jagir Kota Surabaya Provinsi Jawa Timur - Izdiyadatu Mawaddati; Ida Munfarida; Abdul Hakim (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
Kali Jagir is located in Wonokromo District with a total population of 146,785 inhabitants. 24% of land use in the Wonokromo area is a residential area that disposes of domestic waste such as garbage, laundry waste, and other waste into the Surabaya River stream either directly or indirectly. Disposal of domestic waste from residential areas around the Jagir River results in a decrease in water quality, as well as a decrease in the function of the river, and an increase in the pollutant load that will be received by the river. The method used is descriptive quantitative research method. The water sampling point was determined using the purposive sampling method. The data used is primary data from researchers who have conducted quality analysis at three points of Kali Jagir in 2021. Based on the results, the pollution load value of Kali Jagir Surabaya has exceeded the maximum pollution load capacity that can be accepted by water bodies. Total pollution load in Kali Jagir Surabaya based on TSS parameter is 12,360,924.86 kg/day, BOD parameter is 259,169.08 kg/day, and COD parameter is 6,455,103.32 kg/day.